We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
69
1
avatar

\(-3*{e}^{2m-5} -7=-34\)

I don't understand how to get m

 Jan 29, 2019
 #1
avatar+101255 
+1

-3 * e^(2m - 5)  - 7 = -34  

 

Add 7 to both sides

 

-3 * e^(2m - 5) = -27

 

Divide both sides by -3

 

e^(2m - 5)  =  9         tale the Ln of both sides

 

Ln e ^( 2m - 5)  = Ln (9)        and we can write

 

(2m - 5) * Ln e  =   Ln (9)      since Ln e = 1,  we can ignore this

 

2m - 5   = Ln (9)       add  5 to both sides

 

2m =  Ln (9) + 5        divide both sides by 2

 

m = [ Ln (9) + 5 ] / 2  ≈   3.5986

 

 

cool cool  cool

 Jan 29, 2019

22 Online Users

avatar
avatar